PENYELESAIAN SENGKETA KEPEMILIKAN TANAH - Ayu Kemalasari, Ana Silviana*) , Yunanto (Diponegoro Law Journal, 2013)
In essence, the case of land is a conflict of interest (conflict of interest) in the land sector. In issuing a certificate to a process involving the applicant. Both oral and written explanation of the relevant parties have opportunities for fraud. As an example the case in the Land Office of the parcel of Semarang District 329 Sub Bambankerep Ngaliyan Semarang, Central Java Province. Based on these descriptions, the researchers interested in conducting  research entitled: "Land Ownership Dispute Resolution" (SMG PN Case Studies with the object of dispute in Jalan Gatot Subroto Village Bambankerep Ngaliyan Semarang District).Formulation of this research is, Why is the dispute of land in Jalan Gatot Subroto BambankerepVillage Semarang District Ngaliyan it appears? And how the consideration of the judge and  the judge's decision to settle land ownership disputes in Jalan Gatot Subroto Village Bambankerep Ngaliyan SemarangDistrict?Method of approach used in this study is a normative juridical approach. To approach the problem in this study the authors use research is descriptive specifications. Method of presenting the data in a study conducted in a descriptive way. The advice in this study are, solving land disputes can be implemented by alternative mediation or family. And also, the Judge will decide the case in a fair but necessary efforts to prove prior ownership of the land dispute cases filed with the Court.